(untitled) (Research, Society and Development, 2021)
Objective: to investigate in the scientific literature nursing care for women who are victims of sexual violence. Methodology: integrative review of the literature. The main question was: what is the scientific production about nursing care for women victims of sexual violence. The descriptors were: nursing care; sexual offenses and women, and nursing care; alternative term, sexual abuse, carried out in the Virtual Health Library (VHL), by establishing the databases: Latin American and Caribbean Literature on Health Sciences (LILACS), Virtual Nursing Library (BDENF), Online Medical Literature Search and Analysis System (MEDLINE) and Bibliographic Index Español en Ciencias de la Salud (IBECS). After applying the inclusion and exclusion criteria, eight articles were selected for the final sample. Based on the results, a theme was elaborated: Results: nursing care for women who are victims of sexual violence. These showed that there are gaps in relation to the care provided by nursing professionals, either by the form of reception/approach/care, as well as the non-use of specific care protocols, with failures in the referral of cases. Furthermore, it was observed that where a humanized welcome took place, women felt more comfortable to report what happened. Conclusion: it makes it necessary for health professionals, especially nursing, to acquire knowledge about this complex care, training themselves for the effectiveness of actions, taking care of the whole and exposing the woman as little as possible, understanding the complexity of the pain that permeates the physical, which significantly impacts on the emotional and disstructure of her life and way of living.